2015
DOI: 10.1007/s10705-015-9678-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of nitrogen use efficiency and soil nitrate dynamics to soil mulching in dryland maize (Zea mays L.) fields

Abstract: Plastic film (FM) and gravel mulching (GM) have been used extensively to increase dryland agricultural productivity. Understanding mulching effects on nitrogen (N) use efficiency (NUE) and soil nitrogen dynamics is important for optimizing N management strategies. A 3-year field experiment was performed on the Loess Plateau of China to investigate the GM and FM effects on plant N accumulation, N translocation, N harvest index (NHI), NUE and soil NO 3 --N dynamics in dryland maize fields. Compared with the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…This is consistent with the results reported by Liu et al. (2015), who found that plastic mulching resulted in a decrease in soil nitrate‐N in a field experiment in the Northeast of China.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the results reported by Liu et al. (2015), who found that plastic mulching resulted in a decrease in soil nitrate‐N in a field experiment in the Northeast of China.…”
Section: Discussionsupporting
confidence: 93%
“…The content of soil nitrate‐N in the RM+FS and PM treatments decreased year by year in the present study, which shows that more yield is bound to be accompanied by more nitrate‐N consumption. Thus, the amount of nitrate‐N remaining in the soil after winter wheat harvest may decrease, as the winter wheat yield increases (Liu et al., 2015). In the present study, compared to NM, the average nitrate‐N remaining in the soil in the PM and RM+FS treatments was significantly lower than in NM and SM.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable moisture and temperature conditions under plastic mulches also affect plant roots, typically stimulating root development and increasing root exudation ( Li et al, 2004b ; Subrahmaniyan et al, 2006 ; Wang et al, 2016 ). This results in greater nutrient availability for rhizosphere microorganisms ( Subrahmaniyan et al, 2006 ; Lin et al, 2008 ; Maul et al, 2014 ; Liu et al, 2015 ).…”
Section: Indirect Effects Of Plastic Mulches On Soils Via Microclimatmentioning
confidence: 99%
“…The V. unijuga seed nutrient reserves were increased with plastic mulching relative to straw mulching or the control. This variation in V. unijuga seed nutrient reserves might be explained on the basis of root growth, which is necessary for nutrient uptake important for photosynthesis and seed provisioning (Liu et al, 2009; Loik, 2006) and thus affects nutrient dynamics within seeds (Liu et al, 2015; Stone et al, 1999). Increased soil temperature and moisture generated by plastic film mulching (especially the FM treatment) could promote root development (i.e., increased root biomass) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%